STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME TENAGA KEPENDIDIKAN DI SMP NEGERI 01 MARISA - Riyanti Ismail; Darmawati Darmawati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The role of educational staff is very urgent in educational management to improve the quality of higher quality education. This study aims to describe the principal's strategies for improving the professionalism of educational staff at SMP Negeri 1 Marisa. The professionalism of educational staff is a crucial aspect in supporting the effectiveness of school management and the quality of educational administration services. This study used a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation of the principal and educational staff. The results show that the principal implemented various planned and sustainable strategies to improve the professionalism of educational staff, including: (1) creating a collaborative work culture; (2) involving educational staff in various training courses, workshops, and seminars to improve competency and work skills; and (3) building effective communication. Through the implementation of these strategies, there was an increase in work discipline, responsibility, and the ability of educational staff to carry out their duties professionally. Thus, it can be concluded that the success of improving the professionalism of educational staff is highly dependent on the role of the principal as a visionary, communicative leader, and oriented towards human resource development